2021
DOI: 10.3390/ijms22115532
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA, Transcriptome and Degradome Analysis of the Transgenerational Heat Stress Response Network in Durum Wheat

Abstract: Heat stress is a major limiting factor of grain yield and quality in crops. Abiotic stresses have a transgenerational impact and the mechanistic basis is associated with epigenetic regulation. The current study presents the first systematic analysis of the transgenerational effects of post-anthesis heat stress in tetraploid wheat. Leaf physiological traits, harvest components and grain quality traits were characterized under the impact of parental and progeny heat stress. The parental heat stress treatment had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 80 publications
0
7
0
4
Order By: Relevance
“…Concerning DS, this was demonstrated in durum wheat [55], with the involvement of miRNAs in the regulation of ROS scavenging, hormone signaling, and carbon fixation in the next generation, whereas a similar work in rice showed that memory genes involved in hormone synthesis are regulated by long noncoding RNAs [51]. Small RNAs, essentially miRNAs, are also participants in the intergenerational inheritance of heat stress in Brassica napa [56] and durum wheat [57]. The demonstration that both intergenerational inheritance of DNA methylation and a better adaptation to stresses was dependent on active DCL (Dicer Like) genes suggested that siRNAs also participate in an epigenetic memory of abiotic stresses [58] or herbivory attacks [59].…”
Section: Trends In Plant Sciencementioning
confidence: 99%
“…Concerning DS, this was demonstrated in durum wheat [55], with the involvement of miRNAs in the regulation of ROS scavenging, hormone signaling, and carbon fixation in the next generation, whereas a similar work in rice showed that memory genes involved in hormone synthesis are regulated by long noncoding RNAs [51]. Small RNAs, essentially miRNAs, are also participants in the intergenerational inheritance of heat stress in Brassica napa [56] and durum wheat [57]. The demonstration that both intergenerational inheritance of DNA methylation and a better adaptation to stresses was dependent on active DCL (Dicer Like) genes suggested that siRNAs also participate in an epigenetic memory of abiotic stresses [58] or herbivory attacks [59].…”
Section: Trends In Plant Sciencementioning
confidence: 99%
“…The stress-tolerant DBA Aurora genotype and DBA Artemis, another high-yielding Australian durum wheat variety, were also compared. Small RNA, transcriptome and degradome sequencing data integration, showed transgenerational effects of water-deficit and heat stress in these durum wheat genotypes [ 18 , 26 ]. Effects of water-stress in parental and progeny plants of the Australian durum genotypes showed significant biological interactions between water stress-responsive miRNAs and targets, with transgenerational stress tolerance potentially generated through hormone signaling and nutrient metabolism pathways [ 18 ].…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…On the other hand, heat stress treatment applied to the parents produces a positive effect on the progeny plants by increasing chlorophyll content, grain weight, grain number and grain total starch content [ 18 ]. Integrated sequencing analysis, GO and pathway analysis suggested that stress responsive miRNAs and their target genes have functional roles in hormone homeostasis, signal transduction and protein stabilization [ 26 ]. In a different study, the characterization of the miRNAome of durum cv.…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…It was suggested that the cumulative effects of both (heat and drought)stresses has either synergistic , antagonistic or hypo-additive effects on growth, filling of grain and yield factors (Mahrookashani et al, 2017). Reduction in the yield has been observed under combined stress due to the direct effects of interaction of both of these stresses on stomatal movements.…”
Section: Physiological Changes Under Combined Stress Of Heat and Droughtmentioning
confidence: 99%
“…In most of the regions of the world, wheat is said to be a major source of food and animal feed (Sallam et al, 2019). It can be cultivated in a variety of agro-climatic conditions and wheat yields are highly susceptible to environmental and climatic changes (Mahrookashani et al, 2017). Wheat had a origin from in South-Western Asia, but it has widely adaptability which leads to its growth under different agro-climatic zone such as tropical zone, subtropical and temperate zone (Tyagi & Pandey, 2022).…”
Section: Introductionmentioning
confidence: 99%